Assessment of Food Intake and Nutritional Status of Children Attending Montessori School of Pokhara Valley - Lamsal, Alina; Yadav, Dipendra Kumar; Parajuli, Bijaya (Journal of Karnali Academy of Health Sciences, 2023)
Introduction: Childhood is a time of critical growth in which proper nutrition is necessary. Children afflicted by sustained poor nutrition are at greater risk for obesity, mental and emotional health problems and a failure to thrive academically. The objective of this study was to assess the food intake and nutritional status of children attending the Montessori school. Methods: A cross sectional study was carried out among 235 children of 3-5 years from twenty Montessori schools. Data were collected using simple random sampling. A weighed food was recorded from the consumption of children during a day of their stay in the Montessori school along with the observation of food consumption. Results: More than every nine out of ten children (92.8%) didn’t meet calorie requirement. The mean food intake during their stay in Montessori was 368.81±111.89 grams. Mean calorie, fat, protein, retinol and beta carotene intake were 540±150.5 Kcal, 10.04±5.6 grams, 13.25±5.49 grams, 49.76±32.6 grams, 135.75±274.67 grams respectively. Dietary fat (OR=3.7, 95% CI; 1.8- 7.5) and protein consumption (OR=2.2, 95% CI; 1.1- 4.4) were significantly associated with overweight status of children. Conclusion: The number of nutritive foods should be increased so that the children meet adequate amount of nutrient required for the proper growth and development of their body. Since the association between dietary fat and protein intake with overweight condition was observed the excess use of fat providing foods should be limited and protein rich foods should be provided as per the Recommended Dietary Allowance (RDA) of Montessori children.